The Role of CD3, CD20, CD30, and Ki67 Immunohistochemistries in Establishing Mediastinal Gray Zone Lymphoma Diagnosis in 24-years-old Female Patient - hardiyanto, frenky; Pratiwi, Suryanti Dwi; Erawati, Dini Rachma; Isharanto, Artono; Retnani, Diah Prabawati; Pudjo, Herwindo (Malang Respiratory Journal, 2020)
Title: The Role of CD3, CD20, CD30, and Ki67 Immunohistochemistries in Establishing Â Mediastinal Gray Zone Lymphoma Diagnosis in 24-years-old Female PatientAuthor: Frenky Hardiyanto, MD. Pulmonology and Respiratory Medicine Department, Brawijaya University, Malang, Indonesia. Supervisor: Suryanti Dwi Pratiwi, MD, Pulmonologist Consultant, Artono I, MD, Cardiovascular and Thorax Surgeon, Dini Rachma Erawati, MD, Radiologist Consultant, Diah Prabawati R, MD, Patology Anatomy Specialist, Herwindo P, MD, Internal Medicine Specialist.Introduction:. A woman with complaints of shortness of breath, cough, fever, night sweating, decrease of body weight and swelling in face, neck and right arm. Chest x-rays and ct thorax revealed a mass in mediastinum.Case Description: Patient is a 24 years old female with complaints of shortness of breath, cough, fever, night sweating, decrease of body weight and swelling in face, neck and right arm. Chest x rays and CT thorax revealed a mass in mediastinum. Open biopsy on right neck mass and transthoracic FNAB resulting of chronic inflammation, so the patient was diagnosed with glandular tuberculosis and Mediastinal Tumor. Patient was getting worse after one month consuming OAT. Patient was consulted to Cardiovascular and thorax Surgery Department. Patient was performed thoracotomy and debulking. Anatomical pathology was examined from debulking mass, the result of immunohistochemistry was found nodular mediastinal gray zone lymphoma.Discussion: this case it is very difficult to enforce the diagnosis. Patients have done neck FNAB, transthoracic FNAB, open biopsy right neck mass and FOB have not been able to establish diagnosis. Until finally done thoracotomy and debulking in this patient, from immunohistochemistry results obtained nodular sclerosis Hodgkin lymphoma. Collaboration from pulmonologist, radiologist, cardiovascular and thorax surgeon, and patology anatomy specialistÂ  is needed to confirm the diagnosis in these patients.Keywords: mediastinal tumor, mediastinal gray zone lymphoma